Widespread microglial activation in multiple system atrophy. Issue 4 (6th February 2019) - Kübler, Dorothee; Wächter, Tobias; Cabanel, Nicole; Su, Zhangjie; Turkheimer, Federico E.; Dodel, Richard; Brooks, David J.; Oertel, Wolfgang H.; Gerhard, Alexander
Abstract: Background: The pattern and role of microglial activation in multiple system atrophy is largely unclear. The objective of this study was to use [ 11 C] (R) ‐PK11195 PET to determine the extent and correlation of activated microglia with clinical parameters in MSA patients. Methods: Fourteen patients with the parkinsonian phenotype of MSA (MSA‐P) with a mean disease duration of 2.9 years (range 2‐5 years) were examined with [ 11 C] (R) ‐PK11195 PET and compared with 10 healthy controls. Results: Patients with the parkinsonian phenotype of MSA showed a significant ( P ≤ 0.01) mean increase in binding potentials compared with healthy controls in the caudate nucleus, putamen, pallidum, precentral gyrus, orbitofrontal cortex, presubgenual anterior cingulate cortex, and the superior parietal gyrus. No correlations between binding potentials and clinical parameters were found. Conclusions: In early clinical stages of the parkinsonian phenotype of MSA, there is widespread microglial activation as a marker of neuroinflammatory changes without correlation to clinical parameters in our patient population. © 2019 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.